Indonesia’s Policy Response to Malaysian Cultural Claims (2007–2019) - Halim, Abrar; Samry, Wannofri; Anatona, Anatona (Analisis Sejarah, 2025)
This study analyzes Indonesian cultural policy from 2007 to 2019, focusing on implementation, public response, and its impact on international relations. Culture is positioned as strategic for identity, heritage awareness, and diplomacy. Using a qualitative descriptive-historical approach with written, visual, online, and interview sources, findings show that cultural claims encouraged both reactive and proactive measures. The government accelerated UNESCO registrations of Batik (2009), Angklung (2010), and Wayang (2003) to gain legitimacy. Legal frameworks were strengthened through Law No. 11/2010 on Cultural Heritage and Law No. 5/2017 on Cultural Advancement. Internationally, the Indonesian Cultural House (RBI) program became a soft power instrument, involving the diaspora and enhancing diplomacy. Hence, cultural claims act as both challenges and catalysts for sovereignty, regulation, and global cultural strategy.